2011
DOI: 10.1007/s00011-010-0282-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of TP53 and FAS promoter modulate the progression of coronary artery disease after coronary artery bypass grafting: a gender-specific view

Abstract: Patients presenting with polymorphisms of FAS LG, FAS promoter and TP53 have an increased risk of CAD progression, as they have a higher rate of re-interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…We found in our study that the TP53 level was up regulated in ACAT, suggesting that the TP53 gene contributes to the progression of ATH development. These findings further support the idea of Beiras-Fernandez et al (2011), who suggested that polymorphisms in the TP53 gene increased the risk of CAD progression. A previous study also suggested that cellular death by apoptosis occurs within atherosclerotic lesions (Lesauskaite et al, 2003).…”
Section: Discussionsupporting
confidence: 88%
“…We found in our study that the TP53 level was up regulated in ACAT, suggesting that the TP53 gene contributes to the progression of ATH development. These findings further support the idea of Beiras-Fernandez et al (2011), who suggested that polymorphisms in the TP53 gene increased the risk of CAD progression. A previous study also suggested that cellular death by apoptosis occurs within atherosclerotic lesions (Lesauskaite et al, 2003).…”
Section: Discussionsupporting
confidence: 88%
“…it has been already demonstrated that the R variant of p53 is associated with higher risk of recurrence of coronary atherosclerotic disease (5). oxidative stress has long been known to be a part of the pathogenetic mechanism in diabetes type 2 and one of the major factors in development of complications (3,40).…”
Section: Possible Aspects Of Application Of the Mini-panelmentioning
confidence: 99%
“…The growth of VSMCs was caused by the loss of TP53 activity, while the increase of TP53 level can lead to apoptosis of VSMCs. Plaque VSMCs are more susceptible to apoptosis mediated by TP53 than normal VSMCs [38]. The research hypothesized that the serum concentrations of EGF and other cytokines/growth factors may play a signi cant role in the pathogenesis of CHD, which the nal conclusion was as follow: the concentration of EGF in serum of patients with CHD was higher than that in normal people [39].…”
Section: Discussionmentioning
confidence: 99%